Step-by-step explanation:
sqrt(-4) = sqrt(4×-1) = sqrt(4)×sqrt(-1) = 2i
-1, -1 I think is the answer
The difference of five and negative 7.
<span><span>
1.
</span>Which becomes 5 – (-1) = 6. Such that 5 + 1 = 6.</span>
The total number of fruits available.
Three hundred apples
minus thirty oranges.
<span><span>1.
</span>300 – 30 = 270 fruits</span>
The room temperature of thirty degrees Celsius has risen to
fourty-five degrees Celsius. What is the difference of the final and initial temperatures?
<span><span>
1.
</span>45 – 30 = 15</span>
When the ball rose with an acceleration of 2 m/s2 what is
the difference between the ball’s acceleration and the gravitational force that
acted on it?
<span><span>
1.
</span>-10 - 2 = -12 </span>
Answer:
Step-by-step explanation:
If the expression contains 3 terms none of which can combine with any other, the the expression is a Trinomial. An example of such a thing is f(x) = x^2 + 2x + 1.
The x cannot combine with the x^2 nor with the 1. The same can be said for the x^2 and the 1.